1993
DOI: 10.1159/000261511
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Continuous Cultures of Streptococcus mutans with Streptococcus sanguis or with Streptococcus oralis as a Model to Study the Ecological Effects of the Lactoperoxidase System

Abstract: Mixed continuous cultures of Streptococcus species were obtained, using complex carbohydrate (mucin) as a source of nutrients, to study the ecological effects of oxygen and the lactoperoxidase system. S. mutans NCTC10449 was unable to grow as a pure culture on mucin, but attained a significant population size in the presence of S. oralis and S. sanguis strains. The cell densities of the anaerobic mixed cultures decreased when oxygen was supplied, and S. mutans was more suppressed by oxygen than were S. sanguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In this aspect, Hillman & Shivers (1988) showed in a gnotobiotic rat model that the level of A. actinomycetemcomitans colonization in these rats was 45‐fold lower in animals infected with a hydrogen peroxide‐producing S. sanguinis strain when compared with rats infected with a hydrogen peroxide‐deficient mutant of this S. sanguinis strain. Vanderhoeven & Camp (1993) also showed that S. mutans , in co‐culture with S. sanguinis , was more inhibited when hydrogen peroxide was added to the mixture.…”
Section: Resultsmentioning
confidence: 89%
“…In this aspect, Hillman & Shivers (1988) showed in a gnotobiotic rat model that the level of A. actinomycetemcomitans colonization in these rats was 45‐fold lower in animals infected with a hydrogen peroxide‐producing S. sanguinis strain when compared with rats infected with a hydrogen peroxide‐deficient mutant of this S. sanguinis strain. Vanderhoeven & Camp (1993) also showed that S. mutans , in co‐culture with S. sanguinis , was more inhibited when hydrogen peroxide was added to the mixture.…”
Section: Resultsmentioning
confidence: 89%
“…We have examined how certain conditions which emulate those in the oral environment influence hydrogen peroxide synthesis by S. gordonii. Maximal peroxidogenesis is desirable since it seems to be one of the factors in the oral cavity that suppresses the growth of cohabiting cariogenic and periodontal pathogens (16,17,35). Numerous clinical studies have shown that the presence of peroxidogenic streptococci is correlated with the absence of tooth decay and periodontal disease (1,8,9,16,25,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…pathogens listed above are also susceptible to hypothiocyanite ion (OSCN Ϫ ) (7,35). This antimicrobial agent is generated by salivary peroxidase using streptococcal hydrogen peroxide and thiocyanate ion (SCN Ϫ ), a common component of saliva (27).…”
mentioning
confidence: 99%
“…S. mutans is the main micro-organism causing dental caries. S. sanguis indirectly affects the caries process through its competition with S. mutans for the inhabitation of extant oral niches during dental plaque formation (Carlsson, Soderholm, & Almfeldt, 1969;Carlsson, Grahnen, Jonsson, & Wikner, 1970) and also the direct biochemical antagonism in situ (van der Hoeven & Camp, 1993). It has been suggested that the higher the ratio of cariogenic bacteria (such as S. mutans) to non-cariogenic bacteria (such as S. sanguis), the higher the risk of developing dental caries and vice versa (de Stoppelaar, van Houte, & Backer-Dirks, 1969;Loesche, Rowan, Straffon, & Loos, 1975).…”
Section: Introductionmentioning
confidence: 99%